Trogocytosis-mediated immune evasion in the tumor microenvironment - Jeonghyun Kim; Soyeon Park; Jungseo Kim; Yewon Kim; Hong Min Yoon; Bima Rexa Rayhan; Jaekwang Jeong; Alfred L. M. Bothwell; Jae Hun Shin (Experimental and Molecular Medicine)
Abstract Trogocytosis is a dynamic cellular process characterized by the exchange of the plasma membrane and associated cytosol during cell-to-cell interactions. Unlike phagocytosis, this transfer maintains the surface localization of transferred membrane molecules. For example, CD4 T cells engaging with antigen-presenting cells undergo trogocytosis, which facilitates the transfer of antigen-loaded major histocompatibility complex (MHC) class II molecules from antigen-presenting cells to CD4 T cells. This transfer results in the formation of antigen-loaded MHC class II molecule-dressed CD4 T cells. These “dressed” CD4 T cells subsequently participate in antigen presentation to other CD4 T cells. Additionally, trogocytosis enables the acquisition of immune-regulatory molecules, such as CTLA-4 and Tim3, in recipient cells, thereby modulating their anti-tumor immunity. Concurrently, donor cells undergo plasma membrane loss, and substantial loss can trigger trogocytosis-mediated cell death, termed trogoptosis. This review aims to explore the trogocytosis-mediated transfer of immune regulatory molecules and their implications within the tumor microenvironment to elucidate the underlying mechanisms of immune evasion in cancers.